Caring, curing, coping : nurse, physician, patient relationships - Bishop, Anne H., 1935-; Scudder, John R., 1926- (Book collections on Project MUSE., 1985)
A popular conception of medical care is that nurses care, physicians cure, and patients cope. The significant theme that runs throughout this volume is that the fundamental mission of medicine is caring, and curing may be only one component of that broad mission. Each of the chapters speaks to that theme, although each approaches it from a different perspective.